2008
DOI: 10.1007/s10350-008-9335-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Probiotics in Irritable Bowel Syndrome: A Meta-Analysis of Randomized, Controlled Trials

Abstract: Probiotics may improve symptoms of irritable bowel syndrome and can be used as supplement to standard therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(66 citation statements)
references
References 29 publications
(71 reference statements)
1
63
0
1
Order By: Relevance
“…Step 2: we identified 10 meta-analyses and systematic reviews (published between 2008 and 2015) related to probiotic trials in IBS, [18][19][20][21][22][23][24][25][26]28 reporting a total of 44 RCTs with variable number of trials in each of them that increased over the years. One "systematic review" of complementary and alternative therapies in IBS was not comprehensive at all for IBS probiotic trials 18 ; it included only 4 studies that were also analysed and discussed in all other reviews.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Step 2: we identified 10 meta-analyses and systematic reviews (published between 2008 and 2015) related to probiotic trials in IBS, [18][19][20][21][22][23][24][25][26]28 reporting a total of 44 RCTs with variable number of trials in each of them that increased over the years. One "systematic review" of complementary and alternative therapies in IBS was not comprehensive at all for IBS probiotic trials 18 ; it included only 4 studies that were also analysed and discussed in all other reviews.…”
Section: Resultsmentioning
confidence: 99%
“…19,20,23,25,28 One 22 did perform a systematic review instead of a meta-analysis, but nevertheless mixed both groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years many drugs from synthetic or natural sources have been introduced. Most researchers in recent years have focused on phosphodiesterase inhibitors [8], melatonin [9], herbal products [5], and probiotics [10].…”
mentioning
confidence: 99%
“…Two broad metaanalysis studies [10,20] were conducted in recent years with somewhat different concerns about homogeneity of included studies [21]. Despite the diversity in results of the studies, both meta-analyses concluded that probiotics improve symptoms of IBS and thus can be used as a supplement to standard therapy in patients with IBS.…”
mentioning
confidence: 99%